Spotlight on: Professor Anna Leone - Bridging ancient history and heritage preservation across North Africa (2025)
London: Durham University has issued the following news release: Professor Anna Leone is a leading authority on North African archaeology and heritage protection. Her work is driven by her fascination with ...
Keywords: Archéologie – Djebel Nefousa

Italian research in Libya and the Sahara - Mutri, Giuseppina (Historiographie des préhistoriens et paléontologues d’Afrique du Nord, 2023)
Keywords: Archéologie – Djebel Nefousa

Hunters of the mountain : the archaeology of Jebel Gharbi-Nefusa, northwest Libya, from the end of Pleistocene to the Holocene - Barich, Barbara E. (L'Erma di Bretschneider, 2024)
Purchase online the PDF of Hunters of the mountain, Barich, Barbara E., editor -
Publisher: "L'Erma" di Bretschneider
Keywords: Archéologie – Djebel Nefousa

La Libia nord-occidentale nel quadro della Preistoria olocenica del Nord Africa : missione congiunta Libico-Italiana nel Jebel Gharbi-Nefusa - Mutri, Giuseppina; Barich, Barbara E. (Libya antiqua : Annual of the Department of Archaeology of Libya : XVII, 2024, 2024)
Keywords: Archéologie – Djebel Nefousa

In search of the Romans in Jabal Nafusa in surrounding areas - Sjöström, Isabella (Tripolitania in the Roman Empire and Beyond, 2025)
This book provides an up-to-date account of the archaeology, history, economy, urbanism, art, and architecture of the North African region of Tripolitania during antiquity. The essays by international scholars outline current research and the most recent developments in the archaeology of this territory. The strong interdisciplinary character of the texts reflects the expertise of the different authors – from studies of the landscape and urban development, to funerary practices, architecture, military operations and food supply. This timely publication provides a much-needed new assessment of the evolution of this region throughout the Roman and Late Antique period.
Keywords: Archéologie – Djebel Nefousa

Le Peuplement et l'organisation territoriale à Gabal Msallâta (Libye) au bas Moyen Âge : l'exemple du Hisn Salama - Abdouli, Hafed (Archeologia medievale : cultura materiale, insediamenti, territorio, 2021)
Keywords: Archéologie – Djebel Nefousa

L'habitat rupestre del Gebel Garbi (Libia) = The Rock settlements in the Jebel Gharbi (Libya) - Dell'Aquila, Franco; Fiorentino, Giuseppe; Polimeni, Beniamino; Bencini, Claudio (International seminar in Terra Jonica: Rupestrian settlements in the mediterranean region : from archeology to good practices for their restoration and protection, 2012)
Keywords: Archéologie – Djebel Nefousa

New Data on the Late Pleistocene of the Shakshuk Area, Jebel Gharbi , Libya - Mutri, Giuseppina; Lucarini, Giulio (The African Archaeological Review, 2008)
Le Jebel Gharbi constitue la limite septentrionale du haut plateau tripolitain dont l’élément le plus significatif est son imposant escarpement qui, orienté au nord fait face à la plaine côtière de la Gefara. Depuis les années 90, la Mission Archéologique Italo–Libyenne dans le Jebel Gharbi, dirigée par Barbara Barich (Université de Rome « La Sapienza »), a entrepris un projet de recherche à long terme, destiné à l’élaboration de la séquence culturelle de la région. Pendant la campagne de fouilles 2000, une importante zone de sédentarisation, caractérisée par différents niveaux d’occupation anthropique et de nombreux matériels archéologiques a été reconnue immédiatement aux pieds du Jebel, à proximité du village actuel de Shakshuk, entre la plaine de la Gefara et les dépôts alluvionnaires. Ces réserves d’eau pérennes ont permis l’occupation du territoire même pendant les phases plus arides du Pléistocène.
Keywords: Archéologie – Djebel Nefousa

Protecting Libya's Archaeological Heritage - Bennett, Paul; Barker, Graeme (The African Archaeological Review, 2011)
Keywords: Archéologie – Djebel Nefousa

Italian Archaeology in Libya: From Colonial Romanita to Decolonization of the Past - Munzi, Massimiliano (Archaeology under dictatorship, 2004)
Keywords: Archéologie – Djebel Nefousa

Italian Colonial Archaeology in Libya 1912-1942 - Altekamp, Stefan (Archaeology under dictatorship, 2004)
Keywords: Archéologie – Djebel Nefousa

Italian archaeologists in colonial Tripolitania - Munzi, Massimiliano (Libyan Studies, 2012)
This is a contribution to a reassessment of colonial archaeology in Libya, based on the academic and political/ ideological portraits of the archaeologists serving in the Tripolitanian and (from 1936) Libyan Soprintendenza. Italian colonial archaeologists were, often deliberately, instruments of political strategy. They searched for traces of Rome in the nationalistic context of the Libyan War, and sought to reconstruct an idealised vision of the Roman cities during the Fascist Ventennio. The essential continuity between nationalist archaeology of the Liberal period (1910–1922), characterised by the central idea of the civilising force of Rome as a tool of colonial expansion, and the Fascist archaeology of 1922–1943, in which the integration of archaeology with political aims touched on the extreme, sometimes with grotesque results, will be stressed and a chronological overview presented. Negative judgment should be nuanced by placing the colonial archaeology in its historical context, analysing its structure, remembering that its methodological backwardness was shared by metropolitan archaeology, noting the high quality of the restoration work and finally by comparing Italian fieldwork with that of other European excavations in North African or Near Eastern protectorates and colonies. It is not a case of presenting a revisionist interpretation, but of approaching the subject without prejudice.
Keywords: Archéologie – Djebel Nefousa

The Aterian from the Jebel Gharbi (Libya): New Technological Perspectives from North Africa - Spinapolice, Enza E.; Garcea, Elena (The African Archaeological Review, 2013)
Keywords: Archéologie – Djebel Nefousa

Ibāḍī Boundaries and Defense in the Jabal Nafūsa (Libya) - Lauricella, Anthony J. (The Archaeology of Medieval Islamic Frontiers, 2019)
Keywords: Archéologie – Djebel Nefousa

Erratum to: Developing a Collaborative Strategy to Manage and Preserve Cultural Heritage During the Libyan Conflict. The Case of the Gebel Nāfusa - Nebbia, Marco; Leone, Anna; Bockmann, Ralf; Hddad, Mftah; Abdouli, Hafed; Masoud, Ahmed M.; Elkendi, Nader M.; Hamoud, Hassan M.; Adam, Salah S.; Khatab, Moncif N. (Journal of Archaeological Method and Theory, 2016)
Keywords: Archéologie – Djebel Nefousa

American Mission activities in Libya 2005–16: report - Kane, Susan; Raynolds, William; Carrier, Sam (Libyan Studies, 2017)
Abstract This essay outlines the capacity-building work of the American Archaeological Mission to Libya between the years 2005 and 2016. This work was made possible by grants from the US Embassy to Libya, the US State Department Ambassadors Fund for Cultural Preservation (AFCP) and the Bureau of Near Eastern Affairs in Washington, DC. The principles and objectives underlying our capacity-building programme were inspired by the 2003 UNESCO World Heritage Centre Mission Report by Giovanni Boccardi, in particular his recommendation that the Libyan Department of Antiquities obtain training in the best modern cultural heritage management practices via sustained partnerships with external professionals and organisations. يضع هذا التقرير خطوطاً عريضة لبناء القدرات الذي تقوم به بعثة الآثار الأمريكية إلى ليبيا بين الأعوام 2005–2016. إن المنح التي قدمتها السفارة الأمريكية في ليبيا وصندوق السفراء لحماية التراث (AFCP) ومكتب شؤؤون الشرق الأدنى في واشنطن جعل هذا العمل ممكناً. إن المبادئ والأهداف الأساسية لبرنامج بناء القدرات قد استوحيناها من تقرير جيوفاني بوكاردي لبعثة اليونسكو للتراث العالمي، وبالأخص توصيته بأن تقوم دائرة الآثار الليبية بالحصول على أفضل تدريب في إدارة الموروث الثقافي الحديث وذلك عن طريق شراكات مستدامة مع مهنيين ومؤسسات من الخارج .
Keywords: Archéologie – Djebel Nefousa

The Stone Age in Northwestern Libya: Observations Along a Pipeline - Parenti, Fabio; Mengoli, Davide; Natali, Luca (The African Archaeological Review, 2015)
More than 500 km, from the Mediterranean coast to the Hammada al-Hamra, were surveyed in 2002-'03 along the AGIP-Gas pipeline. Several morphological units were crossed: the Jefara, the Jebel Gharbi and the Hammada al-Hamra. This paper reports the location of more than 60 surface sites, with special attention to Lower and Middle Stone Age assemblages, by far the most represented periods. More than 6,500 lithic artifacts have been collected spanning from Mode 1 to the Late Stone Age. The survey was carried out on foot, along a narrow band of around 50 m width for 80 % of the pipeline, representing an extraordinary sample from the coast to the northern desert and, more extensively, in the Wafa area on the Hammada plateau, where stone quarries, fireplaces and important lithic scatters were documented. On the whole, the assemblages, compared with the main Stone Age sites of Northern Africa, seem older in the very southern sector, well into the Hammada, whereas sites on the Jebel cliff and immediately south are dominated by Middle and Late Stone Age cultural traits. The survey proved to be both a good tool for planning development projects and an important occasion for the study of a relevant region of Northern African prehistory. Plus de 500 km du gazoduc AGIP ont été prospectés en 2002-'03, de la côte méditerranéenne jusqu'à la Hammada al-Hamra, sur plusieurs unités morphologiques: Jefara, Jebel Gharbi, Hammada al-Hamra. Cette prospection a permis de décrire plus de 60 gisements de surface, la plupart attribués au Paléolithique inférieur et moyen (phases culturelles le plus fréquemment rencontrées). Plus de 6500 artefacts lithiques ont ainsi été récoltés, de l'Oldowayen au Late Stone Age. La prospection s'est faite à pied, le long d'une bande étroite de 50 m sur 4/5 du parcours, ce qui représente un échantillon extraordinaire, de la côte jusqu'au désert septentrional, et plus en détail dans la région de Wafa, sur le plateau de l'Hammada, où des ateliers de taille, foyers et autres sites de surface ont été trouvés. Les sites sembleraient plus anciens dans la partie méridionale du secteur, bien à l'intérieur de la Hammada. Sur les abords du Jebel, et immédiatement au Sud, les sites du Pleistocène supérieur dominent, Middle et Late Stone Age. Le potentiel archéologique de cette région est analysé dans le cadre de la préhistoire paléolithique nord-africaine.
Keywords: Archéologie – Djebel Nefousa

Libyan Berber Heritage: Jefara, Adrar Nafusa and Hamada al Hamra Cultural Landscapes. A possible new Tentative Candidate for UNESCO List - Bencini, Claudio (Fondazione Onlus, 2013)
Libyan Berber Heritage: Jefara, Adrar Nafusa and Hamada al Hamra Cultural Landscapes. A possible new Tentative Candidate for UNESCO List
Keywords: Archéologie – Djebel Nefousa

Developing a Collaborative Strategy to Manage and Preserve Cultural Heritage During the Libyan Conflict. The Case of the Gebel Nāfusa - Nebbia, Marco; Leone, Anna; Bockmann, Ralf; Hddad, Mftah; Abdouli, Hafed; Masoud, Ahmed M.; Elkendi, Nader M.; Hamoud, Hassan M.; Adam, Salah S.; Khatab, Moncif N. (Journal of Archaeological Method and Theory, 2016)
The paper discusses the potential of a collaborative scheme for the development of a protocol for recording and managing the cultural heritage in Libya. The critical political situation in the country urges the development of cultural heritage
Keywords: Archéologie – Djebel Nefousa

La moschea rupestre di Tnumayat (Gebel Garbi, Tripolitania, Libia) - Dell'Aquila, Franco; Fiorentino, Giuseppe; Bencini, Claudio (Opera Ipogea, 2011)
Wadi Adrar Foundation and Multidisciplinary Study Group “Berber Civility and Vernacolar Architecure” are performing survey missions since 2006 in the Jebel Gabi in Libya, addressed to study archaeological remnants of the ancient autochthonous civility once populating the tripolitanian mountain, to place artefacts in their historical context and finally to disseminate results. Architectural structures both constructed and digged into the rock were asessed, cave dwellings representing the majority of study cases, and showing a wide spectrum of models depending both on the various usage patterns befitting daily life, and on the geological structure of archaeological sites. Hitherto, Wadi Adrar Foundation and Multidisciplinary Study Group “Berber Civility and Vernacolar Ar chitecure” established cooperation toghether with italian Universities of Pisa and Florence, the Mediterra nean University, and with the Alrefak University of Tripoli, costituting working groups that studied, measu red and modeled several abandoned villages, Qasr, single housings and oil mills, all being both constructed or digged into the rock. In the present work the Rock Cave Mosque in Tnumayat is studied in detail, being situated in al-Khirba (the ruins) in the Kabaw neighbourhood. This individual artifact has been selected for the study as it represents an original example of Rock Cave Mosque showing fine digging technique and finely plaster bas-relief decorated interiors. A long inscription situated in the Dromos entrance trabeation allows both construction dating in 454 a.E.-1062 A.D. and customer Abd al-Malik identification. Interior is divided into three naves and a separate area reserved to women is identifiable
Keywords: Archéologie – Djebel Nefousa

Note sul Cristianesimo nel Jebel Nafusa (Libia) - Dell'Aquila, Franco (Quaderni Friulani di Archeologia, 2010)
Remnants of an ancient Christian presence in the Libyan Jebel Nafusa can be found in the oldest Mosques and in their internal inscriptions, as well as in details in their architectural details.
Keywords: Archéologie – Djebel Nefousa

The Latest Research in the Jebel Gharbi (Northern Libya) : Environment and Cultures from MSA to LSA and the First Neolithic Findings - Barich, Barbara E.; Garcea, Elena; Giraudi, Carlo; Lucarini, Giulio; Mutri, Giuseppina (Libya Antiqua, 2010)
Keywords: Archéologie – Djebel Nefousa

Northern Libya in the final Pleistocene : the late hunting societies of Jebel Gharbi - Barich, Barbara E.; Bodrato, Giulia; Garcea, Elena; Conati Barbaro, Cecilia; Giraudi, Carlo (Quaderni di archeologia della Libya, 2003)
Keywords: Archéologie – Djebel Nefousa

Gli ultimi cacciatori e l'origine dei siti pastorali nel Jebel Gharbi (Libia) - Barich, Barbara E.; Lucarini, Giulio (Scienze dell'Antichità, 2005)
Keywords: Archéologie – Djebel Nefousa

Il progetto nel Jebel Gharbi (Libia) : l'ambiente e le culture - Barich, Barbara E. (Scienze dell'Antichità, 2005)
Keywords: Archéologie – Djebel Nefousa

Libyan-Italian Joint Mission in the Jebel Gharbi (Tripolitania) : the Holocene sequence of the Jifarah plain - Barich, Barbara E.; Lucarini, Giulio; Mutri, Giuseppina (Libya Antiqua, 2015)
Keywords: Archéologie – Djebel Nefousa